The Role of Media in Shaping Public Opinion on Religious Tolerance in Religious News in Mass Media - Mokodenseho, Sabil; Jasiah, Jasiah; Muharam, Suhari; Rizaq, Muhammad; Hasibuan, Kalijunjung (Westscience Press, 2024)
This research delves into the intricate relationship between media representations and public attitudes toward religious tolerance in Indonesian mass media. Employing a mixed-methods approach involving content analysis and surveys with SPSS analysis, the study scrutinizes 300 religious news articles and surveys 150 participants. The content analysis reveals diverse themes, framing, and language, while the survey uncovers patterns in media exposure and public perceptions. Comparative analysis provides global perspectives, and the implications and recommendations offer actionable insights. The findings contribute to understanding the dynamics of media influence on religious tolerance, offering valuable insights for media practitioners, policymakers, and future research efforts